c-Met inhibitor NVP-BVU972 induces antiviral protection and suppresses NF-κB-mediated inflammation - Xie, Yunfei; Zhao, Yang; Chen, Xingyu; Jia, Hongli; Wang, Xiao; Liu, Tianyi; Wang, Haocheng; Li, Yang; Guo, Xuefei; You, Fuping (Frontiers in Immunology, 2025)
IntroductionInhibiting viral replication and limiting NF-κB-driven inflammation simultaneously is essential for better antiviral therapy, highlighting the urgent need for a single agent that achieves both functions.MethodsHere, we reported NVP-BVU972 (NVP), a selective c-Met inhibitor, induced a robust antiviral state and inhibited NF-κB-mediated inflammation.ResultsThe dual functions blocked replication of diverse RNA viruses (VSV, EMCV, MHV) and DNA viruses (HSV-1, VACV) and reduced systemic cytokine levels (Il1β, Il6, Tnfα) in vitro and in vivo. Mechanistically, we identified NVP reprogrammed inflammation-related loci by modulating both gene expression and chromatin accessibility, and chaetocin inhibition of H3K9 methylation reversed its antiviral activity.DiscussionThese findings unveil NVP as a promising host-directed agent that simultaneously limits viral propagation and reduces inflammation, and suggest repurposing NVP as a broad-spectrum antiviral.